2012
DOI: 10.1186/1868-7083-4-6
|View full text |Cite
|
Sign up to set email alerts
|

A macroepigenetic approach to identify factors responsible for the autism epidemic in the United States

Abstract: The number of children ages 6 to 21 in the United States receiving special education services under the autism disability category increased 91% between 2005 to 2010 while the number of children receiving special education services overall declined by 5%. The demand for special education services continues to rise in disability categories associated with pervasive developmental disorders. Neurodevelopment can be adversely impacted when gene expression is altered by dietary transcription factors, such as zinc i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 59 publications
0
49
0
2
Order By: Relevance
“…Further, the biological plausibility of these insecticides as a cause of autism has been described and wheat and corn have been identified as the most important sources of OP exposure among U.S. children [19]. However, the temporal trend in total OP insecticide use does not correlate well to the trend in autism.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the biological plausibility of these insecticides as a cause of autism has been described and wheat and corn have been identified as the most important sources of OP exposure among U.S. children [19]. However, the temporal trend in total OP insecticide use does not correlate well to the trend in autism.…”
Section: Discussionmentioning
confidence: 99%
“…In utero, DNA methylation alters expression of multiple proteins through epigenetics [42] and as a result DNA hypomethylation can lead to an epigenetic reprogramming of the fetal brain to adjust to sulfur deficiency [13,14,43]. It has also been demonstrated that parents of children with ASD have the same impairment in sulfur metabolism observed in ASD [44].…”
Section: Asd Sulfur Metabolism Glutathione and Ammoniamentioning
confidence: 78%
“…An association between reduced PON1 activity and autism in the United States was reported in [67]. Factors which might have contributed to this deficiency that were considered included excess dietary high fructose corn syrup (HFCS), insufficient dietary magnesium, and exposure to mercury.…”
Section: Methionine Synthase Reactionmentioning
confidence: 98%